Evaluasi Terhadap Implementasi Kurikulum Merdeka - Ibrahim Ibrahim; Maulana Zakaria; Rani Pratiwi; Marisa Adelia; Desti Flauren Zakira (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This study discusses the evaluation of the implementation of the "kurikulum merdeka" (independent curriculum). Educational institutions are now encouraged to implement a "kurikulum merdeka" that is oriented towards liberation and independence. The "kurikulum merdeka" serves as an educational approach aimed at granting students the freedom to develop their own potentials and interests, as well as preparing them to face real-world challenges. This research falls under the category of literature review, conducted by utilizing literature sources such as books, notes, and research reports from previous studies. Based on the findings and discussions related to the evaluation of the "kurikulum merdeka" in educational institutions, it can be concluded that evaluation is an integral component of the ongoing curriculum process. Steps involved in the evaluation of the "kurikulum merdeka" include establishing evaluation goals, identifying performance indicators, data collection, data analysis, discussion and collaboration, formulation of recommendations, as well as continuous monitoring and evaluation. The evaluation of the "kurikulum merdeka" should involve the participation of all stakeholders and be open to changes and continuous improvement. Thus, evaluation becomes not only a necessity but also an instrument to continually advance educational institutions towards improvement.